Extraction, Isolation, Characterization, and Bioactivity of Polypropionates and Related Polyketide Metabolites from the Caribbean Region - Raúl R. Rodríguez-Berríos; Agnes M. Ríos-Delgado; Amanda P. Perdomo-Lizardo; Andrés E. Cardona-Rivera; Ángel G. Vidal-Rosado; Guillermo A. Narváez-Lozano; Iván A. Nieves-Quiñones; Jeremy A. Rodríguez-Vargas; Keiry Y. Álamo-Diverse; Naiara Lebrón-Acosta; Nataniel Medina-Berríos; Patricia S. Rivera-Lugo; et al. (MDPI AG, 2023)
The Caribbean region is a hotspot of biodiversity (i.e., algae, sponges, corals, mollusks, microorganisms, cyanobacteria, and dinoflagellates) that produces secondary metabolites such as polyketides and polypropionates. Polyketides are a diverse class of natural products synthesized by organisms through a biosynthetic pathway catalyzed by polyketide synthase (PKS). This group of compounds is subdivided into fatty acids, aromatics, and polypropionates such as macrolides, and linear and cyclic polyethers. Researchers have studied the Caribbean region to find natural products and focused on isolation, purification, structural characterization, synthesis, and conducting biological assays against parasites, cancer, fungi, and bacteria. These studies have been summarized in this review, including research from 1981 to 2020. This review includes about 90 compounds isolated in the Caribbean that meet the structural properties of polyketides. Out of 90 compounds presented, 73 have the absolute stereochemical configuration, and 82 have shown biological activity. We expect to motivate the researchers to continue exploring the Caribbean region's marine environments to discover and investigate new polyketide and polypropionate natural products.